Comparative evaluation of efficacy of oxygenation using high flow nasal cannula vs. conventional nasal cannula during procedural sedation for endoscopic ultrasound: A pilot study - Kamalendra Shukla; Badal Parikh; Alok Kumar; Monish Nakra (Wolters Kluwer Medknow Publications, 2021)
Background and Aims: High flow nasal cannula (HFNC) has numerous advantages against conventional oxygen therapy delivery systems. However, there is limited evidence supporting the use of HFNC in endoscopic ultrasound (EUS) under procedural sedation. The aims of this study is to evaluate the efficacy of two different oxygen delivery devices, that is,HFNCand conventional nasal cannula on the oxygenation status of patients during procedural sedation for EUS. Material and Methods: Sixty adult patients undergoing EUS for various ailments were randomized to two groups group HFNC (n=30) and group nasal cannula [NC (n = 30)]. HFNC (AIRVO2, Fisher and Paykel Healthcare, New Zealand) was used on patients in the group HFNC. Respiratory status of the patients was assessed using pulse oximetry, respiratory rate, procedural airway complications, and oxygen therapy adjustments. The endoscopist assessed the ease of performing EUS at the end of the procedure and patient satisfaction score (PSS) was assessed by using a Likert score in the post-anesthesia care unit. Results: SpO2 measurements in the HFNC group during the procedure were marginally better compared to the NC group but this failed to reach statistical significance. Also, no significant association was found between both groups while comparing desaturation events (P = 0.499), patient satisfaction score (PSS) and endendoscopist's satisfaction score (ESS) (P = 0.795). Both the groups were comparable in terms of airway manipulation, use of airway adjuncts, need to increase oxygen flow rate, endoscope removal, apneic episodes, hypotension, and bradycardia. No major complications were observed in either group. Conclusion: HFNC use in patients undergoing EUS is not superior when compared to conventional nasal cannula oxygen therapy. HFNC failed to show any significant impact on decreasing the risk of desaturation events and airway manipulation during the procedure.